2019
DOI: 10.3892/ol.2019.10600
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of LAMA3 with onset and prognosis of ovarian cancer

Abstract: Correlation of laminin subunit α3 ( LAMA3 ) gene with onset and prognosis of ovarian cancer was investigated. In total, 210 ovarian cancer patients who received surgical resection in West China Second Hospital from March 2011 to March 2013 were randomly selected, and another 160 non-ovarian cancer patients who needed ovariectomy were also selected. The relative expression of LAMA3 gene was compared via quantitative polymerase chain reaction (qPCR) in carcinoma tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…LAMA3 encodes laminins that are essential for the formation of the basement membrane and plays an additional role in regulating cell migration and mechanical signal transduction (Castro et al, 2018). Increased level of LAMA3 was reported in pancreatic ductal adenocarcinoma, ovarian and liver cancer (Svoboda et al, 2017;Zhang et al, 2019;Tang et al, 2019;Yang et al, 2019). LAMA3 also provides instruction for making a subunit of a protein called laminin 332, promoting cell migration in cancer cells (Carpenter et al, 2017;Oh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…LAMA3 encodes laminins that are essential for the formation of the basement membrane and plays an additional role in regulating cell migration and mechanical signal transduction (Castro et al, 2018). Increased level of LAMA3 was reported in pancreatic ductal adenocarcinoma, ovarian and liver cancer (Svoboda et al, 2017;Zhang et al, 2019;Tang et al, 2019;Yang et al, 2019). LAMA3 also provides instruction for making a subunit of a protein called laminin 332, promoting cell migration in cancer cells (Carpenter et al, 2017;Oh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…LAMA3 (laminin subunit α3) encodes laminin, which is involved in regulating cell migration [37]. LAMA3 also regulates the expression of different types of cell growth factors that mediate cell proliferation, including KGF (keratinocyte growth factor), EGF (epidermal growth factor), and IGF (insulin-like growth factor) [38]. The LAMA3expression level in tumor tissues and its effect on survival varies between cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…The LAMA3expression level in tumor tissues and its effect on survival varies between cancer types. Lin et al found that the expression level of LAMA3 in tumor tissues was lower than in normal tissues, and the survival times of ovarian cancer patients with LAMA3 overexpression was better than those with low-expression [38]. In PC, the expression level of LAMA3 in carcinoma tissue is upregulated, and patients with high LAMA3 expression have poor outcomes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…LAMA3 is important in development by interacting with other extracellular matrix components. LAMA3 and its variants expressions are exacerbated that increase the motility and invasiveness in ovarian cancer [ 27 , 28 ]. Tang found that LAMA3 is abnormally hypermethylated in ovarian cancer, but the relationship between LAMA3 methylation and chemotherapy resistance in ovarian cancer has not been reported.…”
Section: Introductionmentioning
confidence: 99%